IRON DEFICIENCY ANEMIA IN ELDERLY PATIENTS - Nigora Saidjanovna Shadjanova (Zeta Repository, 2023)
Iron deficiency anemia (IDA) is a serious problem for both scientific medicine and practical health care. In a number of regions of Central Asia and, in particular, in Uzbekistan, this is the most common form of anemia among certain population groups - children, adolescents, women of childbearing age. . The aim of this study is to study iron metabolism in elderly patients suffering from iron deficiency anemia to determine the state of adaptive and adaptive reactions in this category of patients. We examined 25 patients with iron deficiency anemia aged 60 to 74 years. The diagnosis of iron deficiency anemia was verified on the basis of a comprehensive study of hemoglobin level, red blood cell count, color index, iron content, ferritin and transferritin in blood serum.